Media The Mash Monsters. - Anderson, M. (IEEE spectrum)
The paper discusses the recent events regarding mash-up songs and how they react on the copyright law. A mash-up is a song created out of pieces of two or more songs, usually by overlaying the vocal track of one song seamlessly over the music track of another.